Flexible Virtual Synchronous Generator Control for Distributed Generator with Adaptive Inertia. Issue 1 (20th January 2019) - Meng, Jianhui; Wang, Yi; Peng, Jialin; Xu, Lie; Yin, Jun
Abstract: Distributed generators using power electronic converter interface have no inherent inertial response similar to that from the rotating mass of conventional synchronous generators. Virtual synchronous generator (VSG) emulates the behavior of the synchronous generator including system inertia to improve system dynamic performance. Unlike a real synchronous generator, using VSG with proper design, the equivalent inertia of the distributed generator can be controlled in a wider range. In this paper, a flexible virtual synchronous generator (FVSG) control strategy is proposed, with adaptive inertia contributing to a fast and smooth inertial response. The frequency change rate is designed as an adaptive inertia coefficient to flexibly accommodate system inertia with frequency fluctuation rate. Compared with the conventional VSG control, based on fixed inertia coefficient, both inertia support and oscillation suppression are achieved in the proposed control scheme. Moreover, the principles of control parameters design are analyzed in details. Thus, the dynamic response of the system frequency can be substantially improved by the FVSG. Both Matlab/Simulink simulations and prototype tests are implemented to validate the proposed FVSG control strategy on improving system dynamic frequency performance.